Peran Digitalisasi Pelaku UMKM (Usaha Mikro Kecil dan Menengah) dalam mendukung Ketahanan Ekonomi di Masa Pandemi Covid-19 : Studi Kasus Pada Pedagang Kaki Lima (PKL) di Lima Wilayah DKI Jakarta - Allo, Elisabeth Ratu Rante; Runturambi, Arthur Josias Simon; Hanita, Margaretha (Jurnal Keamanan Nasional, 2022)
This study aims to analyze the role of digitalization in Micro, small, and medium enterprises (MSME), the mobile street traders (pedagang kaki lima/PKL) in order to have economic resilience that has an impact on national security. The approach taken is a quantitative method using primary data from a sample of 1409 street vendors in the 2021 DKI Jakarta PKL masterplan study spread across five areas of DKI Jakarta. The survey results show that street vendors, especially in the DKI Jakarta area, are still not optimally utilizing the marketplace in the form of digitizing online marketing. Further steps are needed regarding this problem for street vendors that involve all stakeholders, not only from the DKI Jakarta Provincial Government but also from other banking and private parties in realizing the role of digitizing street vendors which has an impact on national resilience in the economic sector.